Eradicating out-of-school-children: strategies and best practices from alternative education context - Ila Rosmilawati; Moh Fikri Tanzil Mutaqin (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The process and strategy to prevent children from dropping out of school has been carried out systematically in Indonesia. However, when it comes to the strategy for children returning to school still have difficulties, as well as several obstacles and dilemmas to requites the right strategy. The purpose of this study is to examined the strategies of eradicating out-of-school children and the best practices of alternative schools to provide inclusive and free education Qualitative methods were chosen in the research process, primary data collection was carried out through in-depth interviews and focus group discussions (FGD) with 28 informants, includes policy makers, principals, teachers and students. The data was analyzed using thematic analysis. The findings show that a strong decentralized policy is needed to eradicating OOSC. Furthermore, alternative school plays a role in providing open classes for OOSC with unique characteristics. Good practices of OOSC handling and prevention strategies by alternative school can strengthen the roadmap of OOSC governance and handling strategies at the district level. The implication of this study is that the government, academics, society, and the media need to works together so it can enabling children who have dropped out of school to return to school with awareness.